ATTRACTIVENESS OF SERBIAN RETAIL INDUSTRY FOR FOREIGN INVESTORS WITH REFERENCE TO THE COMPANY DELHAIZE GROUP - Stankov, Biljana; Roganović, Milijana; Marjanski Lazić, Sonja (International Journal of Economic Practice and Policy, 2017)
Trade in Serbia is a very attractive economic area for foreign investors. After the manufacturing sector, this area attracted the most foreign investors in the recent years. By participating in macroeconomic indiicators of the Serbian economy, trade contributes to the intensification of country’s economic growth and development and FDI inflows increase, and thus the promotion of capital accumulation. Since 2000 when Serbia faced more intensive coming of foreign investors, retail industry attracted a significant number of foreign investors. Apart from bringing fresh capital, these investors contributed to the development of modern forms of retail trade, as well as the reorientation of retailers who are now increasingly concerned about the needs and wishes of consumer. As a result, they put aside the range and characteristics of the products they sell. One of the biggest foreign investors in Serbia, and certainly the most powerful participant in the retail market, Delhaize Group is a company based in Belgium. Recognizing the benefits of retail trade in Serbia, as well as excellent prospects of its future development, Delhaize Group took advantage of a favorable opportunity and invested in the purchase of the retail chain Delta Maxi, a former regional leader. Consequently, it achieved the biggest market share and enter into competition with other powerful companies such as Agrokor, Mercator and Metro. Delhaize Group is certainly a leading retailer of food and other products in Southeast Europe and in the United States, but it also appears to be a leader of sustainable and ethical business in its field.